2005
DOI: 10.1038/sj.onc.1208393
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPδ expression in a BCR-ABL-positive cell line induces growth arrest and myeloid differentiation

Abstract: CCAAT/enhancer-binding proteins (C/EBPs) are a family of highly conserved transcription factors that have important roles in normal myelopoiesis as well as associated with myeloid disorders. The chronic myelogenous leukemia (CML) cell lines, KCL22 and K562, express exceptionally low levels of endogenous C/EBPs and provide a good model to test the effects of C/EBPs on myeloid differentiation. To explore the possibility that C/ EBPd can promote differentiation in BCR-ABL-positive cells, we generated stable KCL22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 41 publications
3
69
1
Order By: Relevance
“…Previous studies have also suggested that CEBPD plays a vital role in inflammation and inflammatory disease processes (12,13). However, unlike the inflammatory effectors NF-kB and STAT3 that are consistently activated in cancer cells, CEBPD inactivation has been observed in several types of cancer, including cervical and hepatocellular carcinoma (10,14), breast (15), prostate cancer (9), and leukemia (16). In addition to acting as a tumor suppressor, several recent reports have suggested that CEBPD plays an oncogenic role under certain conditions (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also suggested that CEBPD plays a vital role in inflammation and inflammatory disease processes (12,13). However, unlike the inflammatory effectors NF-kB and STAT3 that are consistently activated in cancer cells, CEBPD inactivation has been observed in several types of cancer, including cervical and hepatocellular carcinoma (10,14), breast (15), prostate cancer (9), and leukemia (16). In addition to acting as a tumor suppressor, several recent reports have suggested that CEBPD plays an oncogenic role under certain conditions (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that CEBPD can potentially mediate differentiation because it can respond to all-transretinoic acid (RA) and vitamin D3 treatment (8). Thus, verifying the effects of CEBPD induction in cancer cells could be interesting because CEBPD might be an important target for the development of chemotherapeutic agents.…”
mentioning
confidence: 99%
“…cells (7,8). CEBPD is also involved in regulating proapoptotic gene expression during mammary gland involution (9).…”
mentioning
confidence: 99%
“…In vitro, C/EBPδ inhibits the growth of tumor cell lines, is associated with G 0 growth arrest, or induces differentiation (6)(7)(8), and promotes genomic stability of mouse embryo fibroblasts (MEFs) (9). C/EBPδ expression correlates with low proliferation and histological grade in meningiomas (10) and was in a 70-gene signature predicting better survival of breast cancer patients (11).…”
mentioning
confidence: 99%